Overlapping hearing and communication profiles for the deletion and the RAI1 variant form of Smith-Magenis Syndrome (SMS) - Brennan, Christine; Baiduc, Rachael R. (Journal of communication disorders, 2024)
•Analysis of SMS Patient Registry data reveals overlapping communication phenotype.•Small differences in communication in SMS due to a deletion versus an RAI1 variant.•The RAI1 gene is associated with the SMS speech-language phenotype.•Noted overlap confirms role of the RAI1 gene in speech-language development. Smith-Magenis syndrome (SMS), a rare, genetically linked complex developmental disorder is associated with hearing loss and delays in speech-language development. Approximately 70 % of those with SMS have a genetic deletion within chromosome 17p11.2 and 10 % have a single gene mutation in the same area, known as the RAI1 variant form of SMS. Previous studies presented preliminary comparisons of the phenotype of those with deletion versus the mutation form of SMS, but none focused on hearing, speech-language, and communication profiles. The current study examined patient registry data and compared two groups of individuals with SMS to determine if genetic differences influence the communication phenotype and to determine the importance of the RAI1 gene in hearing, speech, and language abilities in children. Speech-language and hearing data from the international SMS Patient Registry for 33 subjects with SMS were analyzed: 23 with a genetic deletion (SMS (del)) and 10 with an RAI1 mutation (SMS (RAI1)). Hearing status, otopathology findings, early speech-language milestones, mode of communication, intelligibility, vocal quality, language abilities, and literacy skills were analyzed. There were small differences between the groups for hearing status, otopathological findings, mode of communication, voice quality, intelligibility, speech-language abilities, and literacy. Overlap in the speech-language phenotype between groups confirms previous hypotheses that suggest haploinsufficiency of the RAI1 gene is responsible for the SMS phenotype and that the RAI1 gene is critical for speech-language development. Future studies should include direct testing of receptive and expressive language abilities, including analyses of language samples, with larger groups of individuals to replicate and extend the current findings.